Bird Medium: an alternative to Vogel Medium - Robert L. Metzenberg (Fungal Genetics Reports, 2004)
This medium was designed to circumvent some problems that arise in the use of Medium N (Vogel 1964 Am. Naturalist 98:435-446). These are, among others, the presence of high levels of citrate, a chelator which leaves the concentration of calcium and trace elements uncertain; the use of ammonium nitrate, which leaves the actual source of nitrogen ambiguous; the use of MgSO4, which does not allow the experimenter to vary the concentration of magnesium and sulfur independently; the high activity coefficient for the pKa values of citrate, which makes the pH unnecessarily sensitive to ionic strength; the use of sucrose, which leaves uncertain the nature and relative amounts of the hexose(s) being used at any particular moment; the need to use chloroform as a preservative, which results in the gradual depletion of the aqueous phase of complexes of trace elements.